Perceptually Salient Sound Distortions and Apraxia of Speech: A Performance Continuum - Haley, Katarina L. (Am J Speech Lang Pathol, 2017)
PURPOSE: We sought to characterize articulatory distortions in apraxia of speech and aphasia with phonemic paraphasia and to evaluate the diagnostic validity of error frequency of distortion and distorted substitution in differentiating between these disorders. METHOD: Study participants were 66 people with speech sound production difficulties after left-hemisphere stroke or trauma. They were divided into 2 groups on the basis of word syllable duration, which served as an external criterion for speaking rate in multisyllabic words and an index of likely speech diagnosis. Narrow phonetic transcriptions were completed for audio-recorded clinical motor speech evaluations, using 29 diacritic marks. RESULTS: Partial voicing and altered vowel tongue placement were common in both groups, and changes in consonant manner and place were also observed. The group with longer word syllable duration produced significantly more distortion and distorted-substitution errors than did the group with shorter word syllable duration, but variations were distributed on a performance continuum that overlapped substantially between groups. CONCLUSIONS: Segment distortions in focal left-hemisphere lesions can be captured with a customized set of diacritic marks. Frequencies of distortions and distorted substitutions are valid diagnostic criteria for apraxia of speech, but further development of quantitative criteria and dynamic performance profiles is necessary for clinical utility.